ANALISA KEBUTUHAN AIR BERSIH PELANGGAN PDAM KABUPATEN BOALEMO - Utiarahman, Arfan (Sainstek, 2009)
Cleanness water is a real vital requirement for townee, to fulfill amount of water required drinks, bath, cooks, cleans and is including industrial need. In fulfilling clean amount of water required for resident Kabupaten Boalemo, one of them is is levying of cleanness water managed by Perusahaan Daerah Air Minum (PDAM) Kabupaten Boalemo. Intention of this penelitiaan to know cleanness water availability distributed by PDAM Kabupaten Boalemo in fulfilling requirement of its(the brasque. Result Of Research : Based on status category Kabupaten Boalemo as according to guidance of NSPM Kimpraswil is including medium town with number of residents 100.000-500.000 men is 150 ltr/org/hr, hence usage of water average of still be low that is 121 ltr/org/hr. Conclusion : Based on guidance of NSPM Kimpraswil cleanness water distributed by PDAM Kabupaten Boalemo to brasque still be low, this thing is caused by because capacities IPA owned only 30 l/dt, while required 54 l/dt causing is required addition of kapaistas 14 l/dt to fulfill its the brasque cleanness amount of water required.